External treatments for the preventive repair of existing constructions: A review. (30th December 2018) - Sánchez, M.; Faria, P.; Ferrara, L.; Horszczaruk, E.; Jonkers, H.M.; Kwiecień, A.; Mosa, J.; Peled, A.; Pereira, A.S.; Snoeck, D.; Stefanidou, M.; Stryszewska, T.; et al.
Highlights: The different technologies for non-structural repair of concrete are presented. Compatibility between repair product and concrete surface is a critical aspect. Advanced multifunctional solutions with smart properties are being investigated. Several characterization methods are applied for the effectiveness assessing. The development of standardized studies with common testing criteria is important. Abstract: In the present paper different external surface treatments published in the literature as preventive solutions for improving the performance of existing concrete constructions are presented and discussed. They are categorized as repair materials for concrete conservation, protection surface methods against moisture and aggressive agent penetration, injection techniques for crack sealing and preventive repair solutions with smart functionalities. In a final section, the most extended testing methods for evaluating the effectiveness of the different repair solutions are summarized depending on the property to be enhanced: moisture control and resistance against penetration of aggressive agents. The review shows that although several possibilities exist for the repair of the existing constructions, there is a lack of comparative analysis between the different methodologies. SARCOS COST Action CA15202 stablishes as scientific objectives to carry out comparative studies including the most advanced solutions for the external repair of concrete, giving criteria for effectiveness assessment and defining robust and reliable methods for charactering the performance of the repaired structures.